Association of vitamin D gene polymorphisms in children with asthma - A systematic review. Issue 9 (September 2020) - Ashok, Narmada; Kirubakaran, Richard; Saraswathy, Radha
Abstract: Introduction: The association of Vitamin D and children with asthma is known and there are several individual studies on Vitamin D polymorphisms. However, systematic reviews on all vitamin D associated gene polymorphisms have not been done in children with asthma. Objective: To investigate the association of Vitamin D associated gene polymorphisms and asthma in children (0–18 years) by systematic review and meta-analytic approach. Methods: Our search included 20 full text articles of which 15 were case control studies and 5 used family based linkage disequilibrium method. Total of 2491cases and 3682 controls were included in case control studies, with mean age of 9.58 years and 10.16 years respectively. Quantitative and qualitative analysis were done. Results: Quantitative analysis revealed significant association with protective effect of Apa1 polymorphism in allele (OR 0.81 (0.71, 0.91) and homozygous major form (OR 0.83 (0.70, 0.98) and Taq 1 minor allele in homozygous form (OR 0.73 (0.58, 0.92) in children with asthma. However, the minor allele of Apa1(OR 1.21 (1.07, 1.37), Bsm 1 in heterozygous (OR 1.35 (1.07, 1.71) and homozygous minor form (OR 1.95 (1.59, 2.39), major allele of Fok1(OR1.34 (1.17, 1.52) and Taq1 (OR 1.22 (1.08, 1.38) were found to be increasing the odds of asthma. Ethnic variations were noted in subgroup analysis. Qualitative analysis of the polymorphisms of the Vitamin D associated metabolic genes also showed significant associations. Conclusion: Our review shows significant associations with VDR polymorphisms - Apa1, Bsm1, Fok 1, Taq 1, polymorphisms of Vitamin D metabolic genes – CYP27A1, CYP 2R1, CYP 24A1, GC and genes related to Vitamin D response element (VDRE) in children with asthma. Conducting large studies involving various ethnic regions will strengthen our knowledge on the association and aid in targeted interventions for control of asthma in children. Abstract : Biotechnology; Genetics; Asthma in children; Vitamin D associated gene polymorphisms; Single nucleotide polymorphisms